2020
DOI: 10.1017/s1047951119003287
|View full text |Cite
|
Sign up to set email alerts
|

Congenital ductus arteriosus aneurysm in association with MYH11 mutation: a case report

Abstract: Congenital ductus arteriosus aneurysms develop in the third trimester of fetal life, possibly due to abnormal intimal cushion formation or elastin expression in the ductal wall. It is often diagnosed in infants before 2 months of age. Most have a benign course and resolve spontaneously. However, life-threatening complications have been reported. We report a case of large ductal aneurysm diagnosed incidentally in a neonate, in whom there was a novel mutation in the smooth muscle myosin protein gene—MYH11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The patient is of interest for a novel heterozygous variant of MYH11, which manifested phenotypically as aortic aneurysm, Parkinson syndrome, and noncompaction. Whether the detected heterozygous MYH11 variant was actually responsible for the clinical manifestations remains speculative, but several previous studies reported that heterozygous MYH11 variants can be pathogenic (Table 1) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Except for aortic aneurysm [7,8], the other clinical manifestations of the index patient were not reported in association with MYH11 variants.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The patient is of interest for a novel heterozygous variant of MYH11, which manifested phenotypically as aortic aneurysm, Parkinson syndrome, and noncompaction. Whether the detected heterozygous MYH11 variant was actually responsible for the clinical manifestations remains speculative, but several previous studies reported that heterozygous MYH11 variants can be pathogenic (Table 1) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Except for aortic aneurysm [7,8], the other clinical manifestations of the index patient were not reported in association with MYH11 variants.…”
Section: Discussionmentioning
confidence: 96%
“…Chromosomal rearrangements involving the MYH11 gene are associated with acute myeloid leukaemia and sarcoma [2]. Mutations in MYH11 are associated with multisystem disease, predominantly presenting as visceral myopathy (VM) [3], megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) [4,5], chronic intestinal pseudo-obstruction (CIPO) [6], and familial thoracic aortic aneurysm and dissection [7,8] but also with various other features [9][10][11][12][13][14][15][16][17][18][19][20]. Aortic aneurysm, noncompaction, also known as left ventricular hypertrabeculation (LVHT), and Parkinson syndrome have not been reported in association with MYH11 variants.…”
Section: Introductionmentioning
confidence: 99%
“…Maybe a lot of asymptomatic or not serious complication DAAs would be missed. DAA may be observed in patients with connective tissue disorders such as Marfan, Ehlers-Danlos, and Larsen syndromes, Smith-Lemli-Opitz, Trisomy 13, and Trisomy 18, MYH11 mutation [ 3 , 5 7 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital DAA may be identified in infants, children, and adults; published case reports suggest the most common age of diagnosis is less than 2 months. DAA may be observed in patients with connective tissue disorders such as Marfan [6] , Ehlers-Danlos and Larsen syndromes [ 5 , 10 ], Loeys-Dietz syndrome [12] , Smith-Lemli-Opitz, Trisomy 13, and Trisomy 18 [7] , MYH11 mutation [3] . We diagnosed a case of asymptomatic neonatal DAA.…”
Section: Introductionmentioning
confidence: 99%
“…Several theories have been postulated to explain the mechanism of congenital aneurysm formation of the ductus arteriosus [12,29,30]. The ductal aneurysm can resolve spontaneously without complications through the normal physiological constriction of the parietal wall of the duct at birth and or through a thrombus stratification inside the lumen with organization and incorporation of the thrombotic material and fibrotic occlusion [25].…”
Section: Introductionmentioning
confidence: 99%